Seismic performance of Unbonded Fiber-Reinforced Elastomeric Isolators (UFREI) made by recycled rubber. Influence of suboptimal crosslinking. (1st April 2022) - Habieb, A.B.; Formisano, A.; Milani, G.; Pianese, G.
Highlights: Fibre Reinforced Elastomeric Isolators FREIs, experimental and numerical analyses. Utilization of full 3D FE approach for the roll-over evaluation during cyclic tests. Utilization of Yeoh model and Prony series to characterize rubber pads. Identification of the 3D model of the isolator with non-linear spring and dashpot. Preliminary NLDAs on a small masonry building (CDP model) to determine efficacy. Abstract: Seismic base isolation is considered effective to reduce the vulnerability of structures and it represents an optimal retrofitting solution in terms of reliability and effectiveness. Nowadays, one of the most promising devices is the Unbonded Fiber Reinforced Elastomeric Isolator (UFREI), which is considered a low-cost device, thanks to its lightweight, easy installation, and the total absence of steel. The rubber used to assemble the devices must be vulcanized correctly to create the polymer crosslinking to be ready for structural application. All rubber mechanical properties are strongly affected by curing temperature and curing time. In this paper, a series of experimental tests and numerical analyses have been performed to investigate the influence of crosslinking on the seismic performance of UFREIs made of regenerated Ethylene Propylene Diene Monomer (EPDM) combined with glass fiber reinforcement. Two prototypes have been considered, one vulcanized correctly at 150 °C for 40 min and the other at 130 °C for 40 min. Results obtained from Finite Element (FE) cyclic shear tests analysis and nonlinear time history analyses of a preliminary structural application have shown that the devices vulcanized at 130 °C for 40 min, although having suboptimal crosslinking density, are suitable to isolate low-rise masonry buildings properly.